Scoring hypoechogenic areas in one parotid and one submandibular gland increases feasibility of ultrasound in primary Sjögren's syndrome. Issue 4 (12th December 2017) - Mossel, Esther; Arends, Suzanne; van Nimwegen, Jolien F; Delli, Konstantina; Stel, Alja J; Kroese, Frans G M; Spijkervet, Fred K L; Vissink, Arjan; Bootsma, Hendrika
Abstract : Objective: To assess whether ultrasonographic scoring of (i) both parotid and submandibular salivary glands and (ii) all individual components of the Hocevar scoring system, is needed for classifying patients as primary Sjögren's syndrome (pSS). Methods: Ultrasound examination of the major salivary glands (sUS) was performed in 204 consecutive patients clinically suspected (n=171) or diagnosed (n=33) with pSS. Parenchymal echogenicity, homogeneity, hypoechogenic areas, hyperechogenic reflections and salivary gland posterior border were scored in left and right parotid and submandibular glands. Logistic regression analyses were performed to assess which glands and sUS components contributed significantly to classification as pSS or non-pSS according to the 2016 American College of Rheumatology-European League Against Rheumatism (ACR-EULAR) criteria. Results: 116 (57%) patients were classified as pSS, the remaining as non-pSS. Instead of scoring both sides (area under the curve; AUC=0.856, Nagelkerke R 2 =0.526), multivariate analysis showed that sUS scoring of only right (AUC=0.850; R 2 =0.518) or left (AUC=0.852; R 2 =0.511) parotid and submandibular glands is sufficient to predict ACR-EULAR classification. Moreover, all individual components of the Hocevar scoring system significantly predicted classification. Multivariate analysis showed that parenchymal echogenicity and hypoechogenic areas contributed independently to ACR-EULAR classification (AUC=0.857; R 2 =0.539). Scoring these components in one parotid and one submandibular gland highly predicted ACR-EULAR classification (AUC=0.855; R 2 =0.539). Scoring only hypoechogenic areas on one side showed almost similar results (AUC=0.846; R 2 =0.498). Conclusion: sUS examination of parotid and submandibular glands on one side is sufficient to predict classification of patients according to the ACR-EULAR criteria. To further increase feasibility of sUS in outpatient clinics worldwide, only hypoechogenic areas can be scored.